Genome rearrangements in host-range mutants of the polyvalent staphylococcal bacteriophage 812 - Kaspárek, P; Pantůcek, R; Kahánková, J; Růzicková, V; Doskar, J (Folia microbiologica, 2007)
Mutations extended the host range of the polyvalent bacteriophage 812 of the family Myoviridae in up to 95 % of Staphylococcus aureus strains and 43 % of strains of different coagulase-positive and -negative Staphylococcus species. Mutational changes in the genome of several host-range mutants of phage 812 were identified. Host-range mutant 812F1 harbors a deletion in endolysin gene that arose together with intron excision. Four mutants (812i, 812b, 812p, 812F3) harbor deletion in the structural gene orf8 that results from a genome rearrangement associated with intron insertion. This rearrangement was also detected in the genome of the closely related phages U16 and phi131. Another intron was discovered in the recA812 gene in these four mutants. An insertion was found in a non-coding region of the restriction fragment PstI-O of three mutants (812b, 812F3, 812g) and phages U16 and phi131. The above results contribute to the explanation of genetic factors affecting the host range of polyvalent staphylococcal bacteriophages.
Keywords: sekvenční seřazení; Staphylococcus aureus; RNA virová; sekvence nukleotidů; Polymorphism, Restriction Fragment Length; Molecular Sequence Data; molekulární sekvence - údaje; proteiny virových bičíků; genom virový; mutace; endopeptidasy; polymerázová řetězová reakce s reverzní transkripcí; Endopeptidases; Viral Tail Proteins; Reverse Transcriptase Polymerase Chain Reaction; Amino Acid Sequence; Genome, Viral; Base Sequence; Bacteriophages; Sequence Alignment; RNA, Viral; polymorfismus délky restrikčních fragmentů; Mutation; bakteriofágy; sekvence aminokyselin